Strategies and Tactics in Supply Chain Event Management - Ijioui, Raschid; Emmerich, Heike; Ceyp, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book gives unique insights into the Supply Chain Event Management (SCEM) of world-leading companies. Aims, methods, instruments as well as resources and budgets in Supply Chain Event Management are discussed. The reader will gain a strong understanding of the way to deal with problems along the supply chain and how to avoid them. Supply Chain Event Management is a transparent view of the company and all value chain partners and allows to meet timelines with decreased cost and risks.
Conceptual Design and Case Studies of Supply Chain Event Management -- Transparency in Global Supply Chain Networks — Methods and Tools for Integrated Supply Chain Event Management -- Supply Chain Event Management in the Pharmaceutical Industry — Status and Outlook -- Event Based Process Performance Management -- Interfaces @ Supply Chain Event Management -- Proactive Event Management in the Supply Chain of Aircraft Spare Parts -- Supply Chain Event Management: Managing Risk by Creating Visibility -- Supply Chain Risk Management: A Neural Network Approach -- Performance Management in the Value Chain -- Supply Chain Event Management in the Retail Sector — Three Steps to Success -- Design, Implementation and Evaluation of a Performance Measurement System for Virtual Enterprises in the Aerospace Industry -- Usage and Promotion of Employee Potentials in Modern Production Systems -- Added Value by Outsourcing of SCEM Solutions: Background and Technical Basis -- Holistic and Pragmatic Approach on Proactive Supply Chain Event Management -- Supply Chain Event Management (SCEM): A Strategic Application of Business Process Management (BPM) -- Supply Chain Event Management: Innovation in Logistics Services -- SCEM-System to Support the Development of Consumer Promotion -- Dynamic Models for Simulation and Optimization of Supply Networks -- Design of an Organisational Structure to Govern the Dynamic Behaviour of Aviation-oriented Orders with Multiple Priorities -- Focused Interviews -- SCEM at Telecommunications Service Providers — Useful or Superfluous? -- The Change of REFA Methods by Supply Chain Event Management Considering Globalisation -- Supply Chain Event Management by FORD of Europe -- Supply Chain Event Management in the Financial World -- A Personal Field Report -- Supply Chain Event Management & Strategic Networking.
Keywords: Production management; Engineering economics; Engineering economy; Management; Operations Management; Engineering Economics, Organization, Logistics, Marketing; Management